GESTIÓN ADMINISTRATIVA EN “RADIO FLUMINENSE S.A - VARGAS CRUZ, HAMILTON RICARDO (2018)
Radio Fluminense S.A. of the city of Babahoyo was created on November 14, 1980 by Lic. Gustavo von Lippke, owner manager, his first emissions were made in the Aguirre building located in the streets June 5 between Eloy Alfaro and Rocafuerte of the city of Babahoyo, where he remained until 2003. Currently Radio Fluminense S.A is located in the streets Eloy Alfaro # 315 between Av. 5 of June and August 10, 2nd floor, office 202 of the Faytong building. This radio started with a local frequency, that is to say with 250 watts of power and its emissions were with programs regular, simple content and musical spaces, the frequency assigned to operate It was 100.9 FM. Today it has a provincial frequency on the 101.5 FM dial. Radio It started with four workers, the lady. Inés Chang (+), Mrs. Lidia Contreras (+), the Mrs. Azucena Andino and the journalist Gustavo Von Lippke, manager and owner of the radio.